Assessment of grain discoloration in the main rice genotypes of Corrientes Province, Argentina - Dirchwolf, Pamela Maia (2018)
Rice grain discoloration affects grain yield and quality. Corrientes is the main rice producing province in Argentina. Previous studies were carried out in this province, where only panicle incidence (PI) was evaluated. In view of the need to obtain more agronomic parameters to more exhaustively investigate the effects caused by this disease, the present study was carried out to evaluate panicle incidence (PI), percentage of discolored grains per panicle (GD), weight loss (WL), disease severity index (DSI) and sterility (S) in eight rice genotypes. Although PI and GD are estimated as disease incidence, both were significantly different. GD is obtained by the grain-by-grain evaluation, while PI considers a panicle diseased when the latter presents at least one spotted grain; thus, this last method overestimates the disease incidence. The genotype IRGA 424 recorded maximum and minimum GD and S values, which may be explained by different sowing dates in different regions in the province, with their corresponding environmental conditions during the critical period of the infection and during spikelet formation. WL and DSI had lower values than those reported by other authors, which indicates that the effects of rice grain discoloration on these parameters in Corrientes Province, Argentina, are less severe than in other rice cultivating countries.